Vaantje. 2 blauw-witte vaantjes uit arch. Maas. Pet uit archief Kairos. Omslag voor boekje. 4 vaantjes VJB
Vaantje. 2 blauw-witte vaantjes uit arch. Maas. Pet uit archief Kairos. Omslag voor boekje. 4 vaantjes VJB.